Enhancing ELT Classroom Using Moodle E-Learning During the Pandemic: Students’ and Teachers’ Voices - Arlischa Ardinengtyas; Arifin Nur Himawan (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTThe Covid-19 pandemic that started at the end of December 2019 has brought tremendous impacts on education in Indonesia and worldwide. Responding to this situation, the ministry of education appeals to some educational institutions to conduct online learning during the pandemic. SMA Muhammadiyah 2 Yogyakarta is one of the schools which consistently adhered to the regulation by maintaining the learning process through Moodle-based E-Learning. This phenomenological study is designed to explore students’ and teachers’ perceptions toward the implementation of Moodle E-Learning in ELT during the pandemic. The semi-structured interview was conducted to twenty students and three teachers to get the data based on their beliefs, perceptions, experiences, and perspectives toward the phenomenon. Results of this study show that the use of Moodle E-Learning brings benefits to the ELT Classroom. It builds students’ learning interest and contributes to the enhancement of technological and pedagogical aspects in ELT. Comprehensive material and learning sources are beneficial to expand students’ autonomous learning and problem-solving skills. Further, maximizing Moodle E-Learning features such as discussion forum and teleconference can bridge the demand of blended learning. Thus, Moodle E-Learning is a recommended platform for conducting online learning especially during the pandemic. ABSTRAKPenyakit pandemik (COVID-19) yang terjadi pada akhir Desember 2019 membawa dampak yang luar biasa bagi pendidikan Indonesia. Menaggapi situasi tersebut, Kementerian Pendidikan menghimbau beberapa institusi pendidikan untuk melakukan pembelajaran online selama pandemik terjadi. SMA Muhammadiyah 2 Yogyakarta merupakan salah satu sekolah yang konsisten menaati regulasi dengan tetap menjaga proses pembelajaran melalui Moodle E Learning Based. Penelitian ini dirancang di bawah studi fenomenologi untuk mengeksplorasi resepsi siswa dan guru terhadap penerapan Moodle E-Learning di ELT selama penyakit pandemi. Wawancara semiterstruktur di lakukan terhadap dua puluh siswa dan tiga guru untuk mendapatkan data yang tidak terbatas berdasarkan keyakinan resepsi, pengalaman, dan perspektif mereka terhadap fenomena tersebut. Penggunaan Moodle E-Learning membawa beberapa manfaat bagi kelas ELT. Hasil penelitian ini menunjukn bahwa penggunaan Moodle E-Learning meningkatkan minat belajar siswa. Selain itu memberikan konstribusi pada beberapa peningkatan aspek teknologi dan pedagogis di ELT. Materi yang komprehensif, dan sumber belajar bermanfaat untuk mengembangkan pembelajaran otonom siswa dan ketrampilan memecahkan masalah memaksimalkan fitur Moodle E-Learning seperti forum diskusi dan telekonferensi dapat menjembatani permintaan blended learning. Dengan demikian, Moodle E-Learning adalah platform yang direkomendasikan untuk melakukan pembelajaran online.